PENGARUH STANDAR AKUNTANSI PEMERINTAH SISTEM PENGENDALIAN INTERNAL TERHADAP KETEPATAN WAKTU PELAPORAN KEUANGAN PADA BADAN KEUANGAN DAERAH (BKUD) KABUPATEN PINRANG - Pratiwi, Elsa; Jumriani, Jumriani (DECISION : Jurnal Ekonomi dan Bisnis, 2022)
This study aims to determine the effect of the application of the government accounting system and internal control system on the timeliness of financial reporting at the Regional Finance Agency (BKUD) of Pinrang Regency. The data collection techniques used in this research are Observation, Questionnaire, and Measurement Scale. The sample in this study was 66 respondents. The data analysis technique in this study used multiple linear regression analysis. Based on the results of the research that has been done, it shows that: 1) Government Accounting Standards have a positive effect on the timeliness of financial reporting at the Regional Finance Agency (BKUD) of Pinrang Regency. 2) The Internal Control System has a positive effect on the timeliness of financial reporting at the Regional Finance Agency (BKUD) of Pinrang Regency. 3) Government accounting standards and internal control systems have a positive effect on the timeliness of financial reporting at the Regional Finance Agency (BKUD) of Pinrang Regency.